2015
DOI: 10.1186/s40163-015-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

An application of CRAVED to the choice of victim in sexual homicide: a routine activity approach

Abstract: CRAVED-Concealable, Removable, Available, Valuable, Enjoyable, and Disposable-has proven to be a useful model to explain various forms of theft. No attempt has been made to apply this model to interpersonal crimes. The current study proposes that the CRAVED model may be used not only to explain theft but also patterns of sexual homicide. Therefore, the aim of the study is to attempt to use the CRAVED model in order to explain the differences between sexual homicide of children and sexual homicide of adult. Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 28 publications
(34 reference statements)
0
43
0
1
Order By: Relevance
“…Furthermore, SHOs of children were more likely to find the victim at home or outside on the street and to physically beat the victim during the criminal event (Beauregard & Martineau, 2015). A study conducted by Proulx and colleagues (2018) showed that SHOs of children were more likely to use physical violence in order to control the victim, to kill the victim for the purpose of eliminating a witness, and to commit the crime outdoors.…”
Section: Sexual Homicide Of Childrenmentioning
confidence: 99%
“…Furthermore, SHOs of children were more likely to find the victim at home or outside on the street and to physically beat the victim during the criminal event (Beauregard & Martineau, 2015). A study conducted by Proulx and colleagues (2018) showed that SHOs of children were more likely to use physical violence in order to control the victim, to kill the victim for the purpose of eliminating a witness, and to commit the crime outdoors.…”
Section: Sexual Homicide Of Childrenmentioning
confidence: 99%
“…For instance, some studies included both serial and non-serial SHOs, despite these two groups of offenders presenting important differences (see James & Proulx, 2014). Other studies included a mix of victim types in their group of SHOs, merging together female, male, and child victims despite clear differences between these groups (e.g., Beauregard & Martineau, 2015;Beauregard & Proulx, 2007;Beauregard, Stone, Proulx, & Michaud, 2008). Probably the greatest limitation that could be responsible for the inconclusive findings observed in the two reviews discussed above is the fact that previous studies compared groups of SHOs with very heterogeneous groups of NHSOs, including violent and non-violent cases (Healey, Beauregard, Beech, & Vettor, 2016).…”
Section: Differences Between Shos and Nhsosmentioning
confidence: 99%
“…In order to increase the comparability between the cases, we decided to select only those involving a female victim aged 16 years old and more. Most of the research in the field of sexual crime has shown that assaults involving child victims are very different in terms of crime process (see for example Beauregard & Martineau, 2015;Beauregard et al, 2008;Chopin, 2017;Chopin & Beauregard, 2019c;Chopin & Caneppele, 2018, 2019Gravier, Mezzo, Abbiati, Spagnoli, & Waeny, 2010;Proulx et al, 2018).…”
Section: Samplementioning
confidence: 99%
“…Most of SH studies are based on a wide range of SHOs and research tends to confirm the heterogeneity of this type of offender. Recent findings showed that sex offences against children and elderly victims followed a specific crime process (e.g., 40,41,90,91).…”
Section: The Sexual Homicide Of Specific Victimsmentioning
confidence: 99%